2003
DOI: 10.1099/ijs.0.01923-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of Alcanivorax venustensis sp. nov. and reclassification of Fundibacter jadensis DSM 12178T (Bruns and Berthe-Corti 1999) as Alcanivorax jadensis comb. nov., members of the emended genus Alcanivorax

Abstract: Two strains of a novel bacterium were isolated independently of each other, from different depths in the Mediterranean Sea, within a time period of 7 months, using two different isolation approaches that were focused on different objectives. Both strains, designated ISO1 and ISO4T, were halophilic, Gram-negative, strictly aerobic, straight rods that were oxidase- and catalase-positive. Both strains produced mucoid colonies in some defined minimal media and were able to grow with organic acids and some alkanes;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 33 publications
(40 reference statements)
3
41
0
Order By: Relevance
“…The signal intensities of C-3, C-4, C-5, C-6, 6-CH 3 , C-2Ј 2Ј-CH 3 , and C-3Ј were higher than those of the non-labeled compound, and 13 C-13 C coupling of C-3-C-4 (J CC ϭ70 Hz), C-5-C-3Ј (J CC ϭ63 Hz), C-6-6-CH 3 (J CC ϭ54 Hz), and C-2Ј-2Ј-CH 3 (J CC ϭ44 Hz) was observed (Table 1). These results indicated that 6-CH 3 and 2Ј-CH 3 were also from pyruvate, and the incorporation pattern of [2,[3][4][5][6][7][8][9][10][11][12][13] C 2 ] pyruvate into 1 is shown in Fig. 2B, supporting the proposed biosynthesis of 1.…”
Section: Feeding Experiments and Biosynthetic Pathway Ofsupporting
confidence: 53%
See 1 more Smart Citation
“…The signal intensities of C-3, C-4, C-5, C-6, 6-CH 3 , C-2Ј 2Ј-CH 3 , and C-3Ј were higher than those of the non-labeled compound, and 13 C-13 C coupling of C-3-C-4 (J CC ϭ70 Hz), C-5-C-3Ј (J CC ϭ63 Hz), C-6-6-CH 3 (J CC ϭ54 Hz), and C-2Ј-2Ј-CH 3 (J CC ϭ44 Hz) was observed (Table 1). These results indicated that 6-CH 3 and 2Ј-CH 3 were also from pyruvate, and the incorporation pattern of [2,[3][4][5][6][7][8][9][10][11][12][13] C 2 ] pyruvate into 1 is shown in Fig. 2B, supporting the proposed biosynthesis of 1.…”
Section: Feeding Experiments and Biosynthetic Pathway Ofsupporting
confidence: 53%
“…These strains have been shown to be important for the biodegradation of petroleum hydrocarbons in a marine environment, especially under bioremediation conditions [4]. During a series of investigations of new metabolites from marine microorganisms [5,6], we found a novel a -pyrone, alcanivorone (1), from the culture broth of A. jadensis (former name: Fundibacter jadensis [7]). We describe in this paper the production, structural determination, incorporation experiments with stable isotope-labeled sodium pyruvate, and a proposed biogenesis of 1 based on the incorporation experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The genera Alcanivorax and Cycloclasticus include both OHCB, like A. borkumensis, A. jadensis [8,9], A.…”
Section: Taxonomy Of Obligate Hydrocarbonoclastic Bacteriamentioning
confidence: 99%
“…dieselolei [10], C. pugetii [11], and C. oligotrophus [12], and more nutritionally versatile species with less restricted substrate profiles, like A. venustensis and C. spirillensus [9,13]. The three other genera of the OHCB group, despite being represented by numerous members, are monophyletic and represented by the three type species Oleiphilus messinensis [14], Oleispira antarctica [15] and Thalassolituus oleivorans [16].…”
Section: Taxonomy Of Obligate Hydrocarbonoclastic Bacteriamentioning
confidence: 99%
“…The G+C content of the DNA of the type strain is 56.44 mol%. (Fernandez-Martínez et al, 2003); 3, A. hongdengensis A-11-3 T (Wu et al, 2009); 4, A. borkumensis SK2 T (Yakimov et al, 1998). Data for catalase, oxidase, API 20NE and API ZYM for the three reference type strains were obtained from our previous study (Lai et al, 2011).…”
mentioning
confidence: 99%